Aplikasi Pencarian Tempat Nongkrong Daerah Kebayoran Lama dengan Metode LBS (Location-Based Service) menggunakan Android Studio - Yoel Pahala Bangun; NM Faizah; Lucky Koryanto (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
The purpose of this study is to design an Android-based application for finding hangout places in the Kebayoran Lama area using the LBS (Location-based service) method using Android Studio due to the lack of public knowledge about hangout places spread across the Kebayoran Lama area, South Jakarta, so they have to know the name of the Hangout Place. first if you want to search on google maps and ask the local community so it's not time efficient. This application can be run on the Android platform as a means of interface with the user because of the ease and efficiency it has. Besides that, using Android devices is common and has even become a necessity for most people today. During the data collection process, observations were made at the research location involving interviews with the community around Kebayoran Lama, South Jakarta, DKI-Jakarta. At the application development stage using the XP (Extreme Programming) method and the use of Location-Based Service (LBS) as location services and mobile devices. The results of the research in the form of an application to find hangout places in Kebayoran Lama, South Jakarta using the Location-Based Service (LBS) method are expected to help people in Kebayoran Lama, South Jakarta to find locations where to hang out that provide cheap food and drinks, so that it can make it easier for people to use their time efficiently.